Implementing Problem-Based Learning with Differentiated Learning Styles to Improve Higher-Order Thinking Skills - Kharisma Sofiana; Christine Wulandari Suryaningrum; Fatqurhohman Fatqurhohman (Universitas Islam Ahmad Dahlan (UIAD), 2025)
This study aims to develop higher-order thinking skills (HOTS) in tenth-grade students by implementing the Problem-Based Learning (PBL) model combined with differentiated learning according to each student's learning style. Based on initial observations, most students are still at a low level of thinking, tend to rely on memorization, and experience difficulties in analyzing, evaluating, and formulating solutions. The PBL model was chosen because it is able to develop HOTS by presenting real-world problems at the beginning of the lesson as a motivational trigger and context for in-depth investigation. This approach is combined with diverse learning that meets the needs of visual, auditory, and kinesthetic learners. The study was conducted in several cycles, where in the first cycle the learning was designed according to PBL syntax and learning styles, complete with relevant media. Although student engagement increased, some students, especially those with auditory and kinesthetic learning styles, still experienced difficulties in working on HOTS problems. The final results showed significant improvements: 84% of students successfully completed HOTS problems based on analysis and logic, 89% were active in discussions, and more than 80% achieved the Minimum Completion Criteria (KKM). This study concludes that the combination of PBL and differentiated learning is effective in improving students' HOTS, self-confidence, and collaboration skills, making it worthy of being implemented in a more comprehensive manner.